Inhaled or Nebulized Furosemide for Dyspnea in Palliative and Advanced Illness: A Structured Narrative Review - Muhanad Alzahrani; Abdullah Alabbasi; Ziyad Alzahrani (Journal of Palliative Medicine, 2026)
Background: Inhaled or nebulized furosemide has been proposed as a potential therapy for dyspnea based on experimental evidence suggesting modulation of pulmonary afferent signaling and preferential attenuation of air hunger. However, its clinical role in palliative and advanced illness populations remains uncertain. Methods: We conducted a structured narrative review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 reporting guidance. PubMed and Web of Science were searched from inception to February 2025. Studies were eligible if they evaluated inhaled or nebulized furosemide in patients with advanced cancer, end-stage heart failure, or other palliative conditions—defined as conditions at a stage where cure is no longer the primary therapeutic goal and symptom management is the primary intent of care—and reported dyspnea outcomes. Risk of bias was assessed according to study design, and overall certainty of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation framework. Results: Nine studies met inclusion criteria, including one randomized, placebo-controlled three-arm crossover trial, one prospective study, several case reports, and review articles. The only randomized trial demonstrated no significant benefit compared with saline or no treatment. Uncontrolled studies reported subjective improvement but were limited by small sample sizes and high risk of bias. Overall certainty of evidence for dyspnea reduction was low to very low. Conclusions: Inhaled furosemide has biological plausibility but lacks confirmatory randomized evidence in palliative populations. Post-2017 controlled delivery studies further demonstrate that optimizing dose or aerosol technique does not resolve the inconsistent treatment response. At present, inhaled furosemide should be considered investigational pending well-designed clinical trials.